Extent and patterns of morphological and molecular genetic diversity and population structure of Nigerian taro cultivars - Oladimeji, J. J.; Abe, A.; Kumar, P. L.; Agre, A. P.; Ilesanmi, O. J.; Vetukuri, R. R.; Bhattacharjee, R. (2024)
Genetic diversity is crucial for conservation efforts as well as breeding programs targeted at the development of improved varieties. Taro, a climate-resilient crop, plays a vital role in the nutritional and economic livelihoods of many households in Nigeria, but its yield is very low due to inadequate genetic improvement efforts. A diversity assessment of Nigerian taro is therefore required to create a premise for its improvement in yield, quality and disease tolerance. In this study, the genetic diversity and population structure of 490 taro cultivars comprising two main gene pools: Dasheen (215) and Eddoe (275), collected from farmers and marketers across seven states in Nigeria was assessed using 3047 Diversity Array Technology single nucleotide polymorphism (DArT-SNP) markers. A subset of 114 taro cultivars, comprising 30 Dasheens and 84 Eddoes were further phenotyped using 24 agro-morphological descriptors.